Using Functional Trait Diversity Patterns to Disentangle the Processes Influencing the Recovery of Subalpine Grasslands Following Abandonment of Agricultural Use - Zhang, Hui; John, Robert; Liu, Kun; Qi, Wei; Long, WenXing (Frontiers in Ecology and Evolution, 2019)
Grasslands in the Qinghai-Tibetan Plateau, as in much of the world, are increasingly degrading due to agriculture exploitation. Restoring such grasslands or facilitating recolonization to create late-successional communities requires an understanding of how communities within grasslands are structured within a secondary succession series. Here we studied community assembly using species abundance, soil nutrient levels, three functional traits (photosynthesis rate, seed mass and seed germination rate) in two comparable chronosequences of sub-alpine grasslands in the Qinghai-Tibetan Plateau. These grasslands range from ‘natural grassland’ (without human managements), to those that have been excluded from agricultural exploitation for 4 to 13 years. We were interested in shifts in functional trait diversity (FD; the value and range of functional traits in a community) and trait dispersion represented by the differences between observed FD and the expectation under neutral assembly. We found that a series of abiotic and/or biotic filters significantly influenced the success of species in different successional states, leading to systematic shifts in plant life history strategies from traits that indicated high relative growth rate to traits that signified highly competitive ability. We also found comparable community assembly processes between 13-year and natural grasslands, where hierarchical competition led to the exclusion of forb species by graminoid species and facilitation induced by legume species. Our results have three implications for degraded subalpine grasslands caused by agriculture exploitation in Qinghai Tibetan plateau. First, in the course of the abandonment of agricultural use and the return from degraded to natural grasslands, deterministic processes induced a shift in plant strategies from rapid relative growth rate under low N competition to slow relative growth rate under high N competition. Second, active seeding of graminoid and legume species may reduce the hierarchical competition, which in turn speedup recovery from agriculture exploitation. Finally, monitoring FD and trait dispersion patterns may be a good way to evaluate the restoration efforts in degraded grasslands caused by agriculture exploitation in Qinghai Tibetan plateau, due to the close connection of functional attributes (e.g., growth, colonization, recruitment and resource competition) and natural state of this ecosystem.